Evidence for persistence of the SHIV reservoir early after MHC haploidentical hematopoietic stem cell transplantation. Issue 1 (December 2018) - Colonna, Lucrezia; Peterson, Christopher; Schell, John; Carlson, Judith; Tkachev, Victor; Brown, Melanie; Yu, Alison; Reddy, Sowmya; Obenza, Willi; Nelson, Veronica; Polacino, Patricia; Mack, Heather; et al.
Abstract Allogeneic transplantation (allo-HCT) has led to the cure of HIV in one individual, raising the question of whether transplantation can eradicate the HIV reservoir. To test this, we here present a model of allo-HCT in SHIV-infected, cART-suppressed nonhuman primates. We infect rhesus macaques with SHIV-1157ipd3N4, suppress them with cART, then transplant them using MHC-haploidentical allogeneic donors during continuous cART. Transplant results in 100% myeloid donor chimerism, and up to 100% T-cell chimerism. Between 9 and 47 days post-transplant, terminal analysis shows that while cell-associated SHIV DNA levels are reduced in the blood and in lymphoid organs post-transplant, the SHIV reservoir persists in multiple organs, including the brain. Sorting of donor-vs.-recipient cells reveals that this reservoir resides in recipient cells. Moreover, tetramer analysis indicates a lack of virus-specific donor immunity post-transplant during continuous cART. These results suggest that early post-transplant, allo-HCT is insufficient for recipient reservoir eradication despite high-level donor chimerism and GVHD. Allogeneic hematopoietic cell transplantation (allo-HCT) has led to the cure of HIV in one individual, but the underlying mechanisms are unclear. Here, the authors present a model of allo-HCT in SHIV-infected nonhuman primates and show that the SHIV reservoir persists in multiple tissues early after transplantation.